Active play and screen time in US children aged 4 to 11 years in relation to sociodemographic and weight status characteristics: a nationally representative cross-sectional analysis - Must Aviva; Economos Christina D; Anderson Sarah E (BMC, 2008)
Abstract Background The high prevalence of childhood obesity underscores the importance of monitoring population trends in children's activity and screen time, and describing associations with child age, gender, race/ethnicity, and weight status. Our objective was to estimate the proportion of young children in the US who have low levels of active play or high levels of screen time, or who have both these behaviors, and to describe associations with age, gender, race/ethnicity, and weight status. Methods We analyzed data collected during the National Health and Nutrition Examination Surveys 2001-2004, a US nationally representative cross-sectional study. We studied 2964 children aged 4.00 to 11.99 years. Our main outcomes were reported weekly times that the child played or exercised hard enough to sweat or breathe hard (active play), daily hours the child watched television/videos, used computers, or played computer games (screen time), and the combination of low active play and high screen time. Low active play was defined as active play 6 times or less per week. High screen time was defined as more than 2 hours per day. We accounted for the complex survey design in analyses and report proportions and 95% confidence intervals. We used Wald Chi-square to test for differences between proportions. To identify factors associated with low active play and high screen time, we used multivariate logistic regression. Results Of US children aged 4 to 11 years, 37.3% (95% confidence interval, 34.1% to 40.4%) had low levels of active play, 65.0% (95% CI, 61.4% to 68.5%) had high screen time, and 26.3% (95% CI, 23.8% to 28.9%) had both these behaviors. Characteristics associated with a higher probability of simultaneously having low active play and high screen time were older age, female gender, non-Hispanic black race/ethnicity, and having a BMI-for-age ≥95th percentile of the CDC growth reference. Conclusion Many young children in the US are reported to have physical activity and screen time behaviors that are inconsistent with recommendations for healthy pediatric development. Children who are overweight, approaching adolescence, girls, and non-Hispanic blacks may benefit most from public health policies and programs aimed at these behaviors.